Analisis Stabilitas Bendung (Studi Kasus Perencanaan Bendung Di Aliran Sungai Pebendungan) - Sudarmanto Sudarmanto; Siswanto Siswanto; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In order to fulfill the water irrigation requirements for Koto Rajo Irrigation Area, will be planned Pebendungan Weir that can be used to accommodate the additional water supply from Pebendungan River to the Irigation System in Koto Rajo. Weir is transverse building river server to elevate water to be taken down and streamed to a channel throught the building retrieval. The research was using secondary data of daily rainfall during 15 years from Sentajo stations. The forces that counts was gravity itself, seismic force, hidrostatik, uplift pressure and the analysis of the stability of weir stability that counts was the overturning and slip. The results of the study were obtained the design of weir hydraulics plan had been accepted for the conditions of Q50th = 36,946 m3/sec.Height of weir is 1,30 m with circle spillway and widht is 13,62 m. From dimensions of the flood discharge obtained value Froude of 2,34. and been building an megrim vlughter type. Dimensions of weir was safe to overturning and slip that work well during normal water level conditions and maximum water level condition.Keywords: Weir, stability analysis, overturning, sliding